1976
DOI: 10.1042/bj1580583
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine triphosphate-evoked catecholamine release in chromatin granules. Osmotic lysis as a consequence of proton translocation

Abstract: Chromaffin granules suspended in C1-containing media release catecholamine and protein when ATP is added. This phenomenon is inhibited in hyperosmotic media and in the presence of uncouplers of oxidative phosphorylation. Release requires a permeant anion in the medium, but is independent of the cation. The release process appears to be driven by an inwardly directed proton-translocating adenosine triphosphatase. The resulting proton-anion influx causes osmotic lysis of the chromaffin granules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

1977
1977
1988
1988

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(43 citation statements)
references
References 15 publications
3
40
0
Order By: Relevance
“…As observed In many laboratones further purificatlOn of secretory veslcles on sucrose density gradients gives nse to great fragility when Incubated at 37°C. Even for secretory vesicles Isolated only by differential centnfugatlOn leakage dunng Incubation in 300 mM sucrose media was found to be much hlgher [27] than leakage from veslcles punfied further on Percoll gradients (Fig.2). Secretory veslcles further punfied on sucrose-metnzamlde gradients Incubated at 37°C In 300 mM sucrose release about 50% of their content wlthin 5 min, followed by a slow further release over the next hour [28] _ By contrast secretory vesicles recovered from Percoll gradlents release only 7.5% of total adrenalin after 5 mm of InCUbatlOn at 37°C, with a gradual release of further content withIn 1 h (FIg.2).…”
Section: Discussionmentioning
confidence: 99%
“…As observed In many laboratones further purificatlOn of secretory veslcles on sucrose density gradients gives nse to great fragility when Incubated at 37°C. Even for secretory vesicles Isolated only by differential centnfugatlOn leakage dunng Incubation in 300 mM sucrose media was found to be much hlgher [27] than leakage from veslcles punfied further on Percoll gradients (Fig.2). Secretory veslcles further punfied on sucrose-metnzamlde gradients Incubated at 37°C In 300 mM sucrose release about 50% of their content wlthin 5 min, followed by a slow further release over the next hour [28] _ By contrast secretory vesicles recovered from Percoll gradlents release only 7.5% of total adrenalin after 5 mm of InCUbatlOn at 37°C, with a gradual release of further content withIn 1 h (FIg.2).…”
Section: Discussionmentioning
confidence: 99%
“…The integrity of granules during incubations was followed by light scattering measurements at 540 nm [29,30] using a Varian Techtron 635 double-beam spectrophotometer equiped with thermostated cuvettes. In preliminary experiments the extent of lysis was also evaluated by determination of soluble protein released into the incubation mixture.…”
Section: Incorporation Of Exogenous [14c]lysophosphatidylcholine In Imentioning
confidence: 99%
“…There is compelling evidence that the ATPase of the chromaffin vesicle membrane is a H+ pump that can increase the intravesicular H+ concentration (6,7,14). One It has been suggested that catecholamine concentrates within the chromaffin vesicle by the same mechanism as methylamine (4,8).…”
Section: Methodsmentioning
confidence: 99%
“…Membrane 6-fold in this preparation. Because there is strong evidence that the membrane-bound ATPase is a H+ pump, the effects on the H+ concentration gradient were investigated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation